Leishmaniasis: Middle East and North Africa research and development priorities - McDowell, Mary Ann; Rafati, Sima; Ramalho-Ortigão, Marcelo; Salah, Afif Ben (My University, 2011)
Leishmaniasis remains one of the world's most devastating neglected tropical diseases, causing substantial mortality and contributing to nearly 2 million disability-adjusted life years. The true global burden of leishmaniasis, however, is unknown. The Middle East and North Africa (MENA) region is endemic for many forms of leishmanisis and has hosted many recent epidemic outbreaks. A research and policy conference, LEISHMANIA: Collaborative Research Opportunities in North Africa and the Middle East, was held in June 2009 in Tunisia to promote international collaboration between the United States (US) and the countries most affected by Old World leishmaniasis (see Table 1 for a list of participating countries). Supported by the US National Institute of Allergy and Infectious Diseases, National Institutes of Health (NIH), and hosted locally by the Institute Pasteur de Tunis, approximately 100 scientists and administrators from the US and MENA countries met to share critical information and to identify the major obstacles for translating scientific breakthroughs into innovative strategies for reducing the burden of leishmaniasis. The participants identified three crucial areas as requiring reinforcement and growth: translation of laboratory discoveries into field-applications, increased research capacity in endemic countries, and the creation of a leishmaniasis reagent repository (Figure 1). Our hope is that these recommendations will be adopted by research, funding, and policy institutions alike to have a greater impact at controlling leishmaniasis throughout the world.
Citation: McDowell, M., . . . & Salah, A. (2011). Leishmaniasis: Middle East and North Africa Research and Development Priorities. PLoS Neglected Tropical Diseases, 5(7), e1219. https://doi.org/10.1371/journal.pntd.0001219
Keywords: Leishmaniasis; Tropical diseases; Middle East; North Africa; Research